(untitled) (Research, Society and Development, 2023)
Introduction: Iatrogenic pseudomeningocele is a tear of the dural sac resulting in cerebrospinal fluid (CSF) leakage during spinal surgery such as repair for a herniated disc. It is a cyst covered by fibrous tissue and filled with CSF, being symptomatic or asymptomatic. In this sense, this surgical complication with great harm to the patient, such as post-surgical pain symptoms, should be highlighted. Objective: Narrative review of the published literature on the subject, seeking to gather and synthesize knowledge. Method: literature review with searches in the Virtual Health Library/MEDLINE, CINAHL, Web of Science and Scopus CAPES databases, with the Medical Subject Headings (MeSH) descriptors: “pseudomeningocele”, “adult”, “laminectomy”, associated by the Boolean AND operator, from 2005 to 2021. A total of 92 articles were found, 14 of which were duplicates and 5 were triplicates. Of the 49 articles found, 18 were included, with the aim of answering the guiding question based on the reading in full: “What are the clinical manifestations, diagnoses and treatments used to identify, treat and predict prognosis for patients with pseudomeningocele?”. Results and discussion: cases of pseudomeningocele are asymptomatic, small and spontaneously regress. In symptomatic patients, it is manifested by headache, lumbar pain and radiculopathy. These are risk factors: invasive techniques, use of epidural triamcinolone acetonide, laminectomy and advanced age, foraminectomy, lateral approach and fusion were protective factors. Treatment for asymptomatic patients is conservative; symptomatic, surgical revision for dural repair is recommended. Conclusion: Therefore, its understanding is important to reduce the occurrence and make patients aware of their risk during spinal surgeries.